Determination of PV Generator I-V/P-V Characteristic Curves Using a DC-DC Converter Controlled by a Virtual Instrument - E. Durán; J. M. Andújar; J. M. Enrique; J. M. Pérez-Oria (International Journal of Photoenergy)
A versatile measurement system for systematic testing and measurement of the evolution of the I-V characteristic curves of photovoltaic panels or arrays (PV generators) is proposed in this paper. The measurement system uses a circuit solution based on DC-DC converters that involves several advantages relative to traditional methods: simple structure, scalability, fast response, and low cost. The measurement of the desired characteristics of PV generators includes high speed of response and high fidelity. The prototype system built is governed by a microcontroller, and experimental results prove the proposed measurement system useful. A virtual instrument (VI) was developed for full system control from a computer. The developed system enables monitoring the suitable operation of a PV generator in real time, since it allows comparing its actual curves with those provided by the manufacturer.